The feasibility and preliminary efficacy of narrative exposure therapy on post-traumatic stress disorder among Syrian refugees in Jordan - Nadeen Smaik; Leigh Ann Simmons; Bayan Abdulhaq; Latefa Ali Dardas (Elsevier, 2023)
Objectives: Post-traumatic stress disorder (PTSD), anxiety, and depression are common mental health disorders among refugees, and all require immediate mental health support to prevent short- and long-term detrimental health outcomes. The purpose of this study was to evaluate the feasibility and preliminary efficacy of narrative exposure therapy (NET) in reducing symptoms of PTSD, depression, and anxiety among Syrian refugees residing in Jordan. Methods: A two-arm randomized control trial was utilized. A total of 40 Syrian refugees aged 18 to 64 diagnosed with PTSD were randomly allocated to either the NET intervention group (n = 20) or the waitlist control group (n = 20) using a computer-generated allocation list with 1:1 allocation. PTSD symptoms were evaluated using the Arabic rendition of the Harvard Trauma Questionnaire, while depression and anxiety symptoms were appraised using the Arabic adaptation of the Hopkins Symptoms Checklist-25. Descriptive statistics were employed to characterize the sample and survey data. Independent t-tests were conducted to assess mean score differences in PTSD, anxiety, and depression between the intervention and control groups. Results: Post NET intervention, significant reductions in PTSD (t = −10.00, P < 0.001), anxiety (t = −9.46, P < 0.001), and depression (t = −6.00, P < 0.001) scores were observed in the intervention group compared to the control group. Effect sizes were moderate for the trauma (Cohen's d = 0.73) and depression (Cohen's d = 0.79) symptoms and notably large for anxiety symptoms (Cohen's d = 0.97). There were no adverse events related to study participation. The intervention achieved a 100% participant retention rate. Conclusions: The results pertaining to retention rate, adherence to the study protocol, data completeness, cultural congruence, and participants' satisfaction provided strong support for the future implementation of the full-scale RCT. NET may be a feasible and helpful approach for refugees and other patients with PTSD, anxiety, and depression.